Natural Clinopyroxene Reference Materials for in situ Sr Isotopic Analysis via LA-MC-ICP-MS - Zhao, Han; Zhao, Xin-Miao; Le Roux, P. J.; Zhang, Wen; Wang, Hao; Xie, Lie-Wen; Huang, Chao; Wu, Shi-Tou; Yang, Jin-Hui; Wu, Fu-Yuan; Yang, Yue-Heng (Frontiers in Chemistry, 2020)
Clinopyroxene is a major host for lithophile elements in the mantle lithosphere, and therefore its origin is critical for constraints on mantle evolution and melt generation. In situ Sr isotopic measurement of clinopyroxene has been available since the rapid development of laser ablation multi-collector inductively coupled plasma mass spectrometry (LA-MC-ICP-MS) in the 2000s. Therefore, there is a growing demand for natural clinopyroxene reference materials for in situ Sr isotope analysis. In this contribution, we present six natural clinopyroxene reference materials from South Africa (JJG1424) and China (YY09-47, YY09-04, YY09-24, YY12-01 and YY12-02) for Sr isotope microanalysis. The Sr content of these clinopyroxenes ranges from 50 μg g-1 to 340 μg g-1, which covers most natural clinopyroxene compositions. Homogeneity of these potential reference materials were investigated and evaluated in detail over a two year period using 193 nm nanosecond and 257 nm femtosecond laser systems coupled to either a Neptune or Neptune Plus MC-ICP-MS. Additionally, the major and trace element of these clinopyroxenes were examined by EPMA, as well as solution and laser ICP-MS. The in situ 87Sr/86Sr values obtained for the six natural clinopyroxene reference materials are in good agreement with data obtained using the TIMS method. The Sr isotopic stability and homogeneity of these clinopyroxenes make them potential reference materials for in situ Sr microanalysis to correct instrumental fractionation, or as quality control materials for analytical sessions. The new Sr isotope data provided here might be useful for in situ and bulk analysis in the geochemical community.